A Comparison of Two Regimens for Managing Sickle Cell Pain and Reducing Readmissions. (3rd July 2021) - Cheng, Elizabeth; Floroff, Catherine; Ingemi, Amanda Irene; Vasist, Neal; Ko, Allen; Goodman, Benjamin Mitchell
Abstract: This was a multicenter retrospective analysis comparing intravenous push (IVP) analgesia versus patient-controlled analgesia (PCA) in patients admitted for sickle cell pain crisis. The primary objective was to compare the analgesic management, measured in total daily morphine milligram equivalents (MME). Secondary objectives included length of hospitalization, 30-day hospital readmissions and pain scores. Of the 98 patients identified between August 2017 and August 2018, 68 patients were included in this study. There were 51% ( n  = 35) in the IVP group and 49% ( n  = 33) in the PCA group. The majority of patients were on 90 or more daily MME prior to admission. The average total daily MME was significantly higher in patients on PCA compared to IVP on the first three days of hospitalization (289 vs 146, p  < 0.01). Length of hospitalization was not different between patients on IVP and PCA (7.14 vs. 6.39 days, p  = 0.53). There was no difference in 30-day readmissions, average pain scores on days 1–3 of hospitalization and adverse side effects between the groups. This study showed patients on IVP had significantly lower total daily MME requirements compared to PCA within the first three calendar days of admission.